2020
DOI: 10.1186/s13041-020-0556-y
|View full text |Cite
|
Sign up to set email alerts
|

Posterior parietal cortex mediates fear renewal in a novel context

Abstract: The return of fear following extinction therapy is an important issue associated with the treatment of many fearrelated disorders. Fear renewal is a suitable model, with which context-dependent modulation of the fear response can be examined. In this model, any context outside of an extinction context (e.g., novel or familiar contexts) could evoke relapse of the fear response. However, brain regions associated with context-dependent modulation are not fully understood. The posterior parietal cortex (PPC) is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Some studies have investigated the metabolites and pathways that are differentially regulated in the prefrontal cortex and nucleus accumbens as well as AMG and HPC in social defeat stress and chronic restraint stress models of mental disorders [34,42]. Although the PPC is implicated in fear learning and memory [29,43], the metabolites and metabolic pathways that are affected in PPC remain unknown. In our study, UPLC-MS/MS based metabolomics analysis data showed that purine metabolism, pantothenate and CoA biosynthesis, glutathione metabolism, and NAD + -dependent signaling were the most perturbed pathways in retrieval of conditioned fear memory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have investigated the metabolites and pathways that are differentially regulated in the prefrontal cortex and nucleus accumbens as well as AMG and HPC in social defeat stress and chronic restraint stress models of mental disorders [34,42]. Although the PPC is implicated in fear learning and memory [29,43], the metabolites and metabolic pathways that are affected in PPC remain unknown. In our study, UPLC-MS/MS based metabolomics analysis data showed that purine metabolism, pantothenate and CoA biosynthesis, glutathione metabolism, and NAD + -dependent signaling were the most perturbed pathways in retrieval of conditioned fear memory.…”
Section: Discussionmentioning
confidence: 99%
“…The fear conditioning procedure was performed in accordance with a previous protocol [43]. For the retrieval test, the context and day conditions of the procedure were modi ed because fear extinction training was not required.…”
Section: Fear Conditioning Proceduresmentioning
confidence: 99%
“…Similarly, adeno-associated virus carrying halorhodopsin was injected 3 weeks before behavioral training into the posterior parietal cortex (PPC) (Joo et al, 2020), which receives diverse sensory and cognitive inputs (Andersen and Buneo, 2002;Morcos and Harvey, 2016;Raposo et al, 2014) and integrates multisensory signals (Andersen and Buneo, 2002;Najafi and Churchland, 2018;Song et al, 2017). Sensory information is processed by the PPC and transformed into behavioral outcomes.…”
Section: Optogenetic Manipulation Effects On Long-lasting Fear Attenu...mentioning
confidence: 99%
“…Recent findings indicate that the PPC plays important role in memory updating. The PPC modulates fear memory renewal after the extinction in fear conditioning 19 . The PPC represents past sensory history and influences behavioral outcomes upon current experience 20 .…”
Section: Introductionmentioning
confidence: 99%